Using Citation Analysis to Assess the Impact of Journals and Articles on Contemporary Accounting Research (CAR) - Brown, Lawrence D.; Gardner, John C. (Journal of Accounting Research, 1985)
Accounting research, Citations, Contemporary accounting research